Mobile Enterprise Transition and Management - Unhelkar, Bhuvan (Auerbach Publications, 2009)
Addressing the rapid evolution of global communications, this book provides step-by-step guidance on how to configure, enact, and manage the process of integrating mobile technology within an organization. The mobile enterprise transition (MET) process presented considers input from the four significant dimensions of an organization - economic, technical, process, and social - making it a well-rounded and complete process. Based on extensive research, literature review, and practical experimentation, this comprehensive text presents emerging best practices, exhaustive case studies, and examples of successful transitions. It also provides detailed references, and a glossary of key terms and commonly used acronyms.
Online resource; Title from title page (viewed June 25, 2009)
Keywords: Mobile commerce; Wireless communication systems; Mobile communication systems; Commerce mobile; Transmission sans fil; Radiocommunications mobiles